Education, Pedagogy, and Identity: The notion of historical, political, and sociopolitical experiences of Indonesia in educational research - Wipsar Siwi Dona Ikasari (Universitas Negeri Yogyakarta, 2020)
Schooling and education are situated contexts to understand issues of identity, culture, representation, and agency (Giroux, 1996). Schools are shaped by specific cultural practices and values which reflect the norms of a particular society for which they have been developed (Hollins, 1996). For example, education and schooling in Indonesia is one of the situated contexts to scrutinize the concept of ‘Indonesian young girls’ and ‘Indonesian schoolgirls’ (Muthali’in, 2001; Blackburn, 2004; Smith-Hefner, 2005). Using the conceptual frameworks of gender, identity and schooling, the schoolgirls identify themselves of being Indonesian girls shaped by their ethnic and religious affiliations. The inextricable link between ethnicity and religion in Indonesia has been continuously shaped within the historical, cultural politics in Indonesia, from the ancient time, the Old Order, New Order, Reformation and Post-Reformation Era. Within the Indonesian context, religious values and social norms hold by the society is important because cultural development contributes to the image of Indonesia as a country (Junarsin, 2009). Keywords: Indonesian schoolgirls, academic achievement, identity, education